2021
DOI: 10.1016/s0140-6736(21)00534-1
|View full text |Cite
|
Sign up to set email alerts
|

Parental education and inequalities in child mortality: a global systematic review and meta-analysis

Abstract: Background The educational attainment of parents, particularly mothers, has been associated with lower levels of child mortality, yet there is no consensus on the magnitude of this relationship globally. We aimed to estimate the total reductions in under-5 mortality that are associated with increased maternal and paternal education, during distinct age intervals.Methods This study is a comprehensive global systematic review and meta-analysis of all existing studies of the effects of parental education on neona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
0
6

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(88 citation statements)
references
References 66 publications
(90 reference statements)
6
63
0
6
Order By: Relevance
“…This was the case for smoking, height and weight, and sporting activities, but also for educational level and occupational status. Some previous studies have reported that the impacts of mothers and fathers on adolescents’ health can be different [ 49 , 79 ]. Regarding the explanation of the inequalities in SRH by familial determinants, the relationship with the father [ 49 ] as well as the father’s support [ 23 ] were found to be particularly important.…”
Section: Discussionmentioning
confidence: 99%
“…This was the case for smoking, height and weight, and sporting activities, but also for educational level and occupational status. Some previous studies have reported that the impacts of mothers and fathers on adolescents’ health can be different [ 49 , 79 ]. Regarding the explanation of the inequalities in SRH by familial determinants, the relationship with the father [ 49 ] as well as the father’s support [ 23 ] were found to be particularly important.…”
Section: Discussionmentioning
confidence: 99%
“…2014 [82]). Other studies still, find no significant association at all (Babic et al, 2017[83]; Baker and White, 2011 [84]; Bruggeman et al, 2019[85]; Leung, 2014[86]).…”
Section: Life Onlinementioning
confidence: 98%
“…For instance, a 2021 global systematic review and meta-analysis highlighted that maternal education is a stronger predictor of child mortality than paternal education. 31 …”
Section: Specific Considerationsmentioning
confidence: 99%